Planning and Budgeting for Women's Empowerment in India: A Historical Process. Issue 1 (June 2019) - Mitra, Sona
This article is an overview of the Indian planning exercise from the lens of women. It provides a historical examination of the overall plan process in India, beginning from the First Five Year Plan and how it journeyed through the several plans to finally integrate with the women's question in India and connect with the larger women's movement. The article traces the emergence of gender responsive budgeting as part of the process financing the development of women. It argues that while the Planning Commission has been abolished, yet the historical significance of planning for women still remains and the experiences can be used to adopt a more inclusive process of gender responsive budgeting, rather than having a narrow and targeted approach to financing for women's needs.